NO Dissociation on Platinum and Platinum-Rhodium Alloy: A Theoretical Investigation - Vu, Khanh Bao; Phung, Khoa Thanh; Thong, Le Hoang; Linh, Bui Thi; Huyen, Nguyen Ngoc (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
In this computational study, the preferential adsorption and co-adsorption sites of various chemical species (N, O, and NO) on the Pt (111) and Rh3Pt (111) surfaces were identified. The preferential adsorption site for NO and co-adsorption sites for N and O on the Pt (111) surface are the hollow (fcc) sites; and these on the Rh3Pt (111) surface are the hollow (fcc1) site and hollow N(hcp2)-O(fcc1) sites, respectively. The activation energies of the NO dissociation reaction on the Pt (111) and Rh3Pt (111) catalytic surfaces are 2.35 and 2.02 eV, respectively. The lower activation energy of the NO decomposition on the Rh3Pt (111) surface is explained by the stronger back-donation from the 4d orbital of the Rh atoms to the 2π* anti-bonding orbital of the NO molecule. The activation energies of the N and O recombination reaction on the Pt (111) and Rh3Pt (111) catalytic surfaces are 1.51 and 2.30 eV, respectively. The study indicates that the Rh3Pt (111) surface not only facilitates the NO decomposition but also better prevents N and O from recombination. Copyright © 2024 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).